2019
DOI: 10.3390/tropicalmed4020060
|View full text |Cite
|
Sign up to set email alerts
|

Policy and Science for Global Health Security: Shaping the Course of International Health

Abstract: The global burden of infectious diseases and the increased attention to natural, accidental, and deliberate biological threats has resulted in significant investment in infectious disease research. Translating the results of these studies to inform prevention, detection, and response efforts often can be challenging, especially if prior relationships and communications have not been established with decision-makers. Whatever scientific information is shared with decision-makers before, during, and after public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 71 publications
0
12
0
3
Order By: Relevance
“…Furthermore, and related to the already mentioned narrow scope of inquiries, generally acknowledged frameworks for the evaluation of response attempts are missing, which makes it difficult to apply results to other settings and outbreaks [ 19 ]. It has also been shown that relevant research on infectious diseases and health security issues often does not reach political decision-makers [ 20 ].…”
Section: Research On Epidemic Response and Response Failuresmentioning
confidence: 99%
“…Furthermore, and related to the already mentioned narrow scope of inquiries, generally acknowledged frameworks for the evaluation of response attempts are missing, which makes it difficult to apply results to other settings and outbreaks [ 19 ]. It has also been shown that relevant research on infectious diseases and health security issues often does not reach political decision-makers [ 20 ].…”
Section: Research On Epidemic Response and Response Failuresmentioning
confidence: 99%
“…Es hat sich zudem gezeigt, dass relevante Forschungsergebnisse zu Infektionskrankheiten und Fragen der Gesundheitssicherheit oft nicht bei Personen mit politischer Entscheidungskompetenz ankommen (Berger et al. 2019 ).…”
Section: Reaktion Auf Epidemien Und Ihr Versagen: Der Forschungsstandunclassified
“…The pandemic of the SARS-CoV-2 virus (also commonly referred to as COVID-19 pandemic by the name of the disease it induces) put a spotlight on the need for mechanisms that can rapidly identify and integrate relevant information to give a fighting chance to the medical and research community. The Ebola and Zika outbreaks presented similar challenges, and significant advances have been made in the past years in terms of digital, laboratory, and epidemiological techniques [1]- [3]. Although numerous resources covering many aspects of pertinent biomedical research have been developed and made publicly available, e.g.…”
Section: Introductionmentioning
confidence: 99%